Gamification and Student Engagement: Evidence, Challenges, and Future Directions - Irvani, Asep Irvan; Dewi, Andani Putri; Gunawan, Aditia Gustiana; Rahmaniar, Andinisa (Eduscape : Journal of Education Insight, 2025)
This narrative review explores gamification as a pedagogical strategy in higher education, highlighting its role in improving student engagement, learning outcomes, and motivation. Literature was collected from Scopus, Web of Science, ERIC, and Google Scholar using keywords such as “gamification and student engagement,” “game-based learning in higher education,” and “gamification and learning outcomes.” Inclusion criteria emphasized empirical and theoretical studies published between 2010 and 2025. Findings show that gamification enhances participation, satisfaction, and academic performance by fostering both intrinsic and extrinsic motivation. Comparative evidence indicates stronger results in developed countries supported by robust digital infrastructure, while limited resources constrain adoption in developing regions. Cultural contexts also matter: competitive elements thrive where recognition is valued, while collaborative gamification proves more effective in cooperative cultures. The results align with Self-Determination Theory and Flow Theory, demonstrating how gamification supports autonomy, competence, and deep engagement. Challenges remain in ensuring equitable access, sustaining long-term impact, and addressing design limitations. Policy support through infrastructure, teacher training, and institutional investment is crucial. Future research should emphasize longitudinal evaluations, adaptive frameworks, and low-tech innovations to foster inclusivity and sustainability. Overall, gamification holds significant potential to transform higher education when integrated thoughtfully within systemic and cultural contexts